معلم الطور الابتدائي بين متطلبات المهام ومصادر ضغوط العمل دراسة ميدانية ببعض مدارس البوني ــ عنابة ــ - لعريط, بشير; بوساحة, عبلة (Université de M'sila, 2018)
الملخص: تهدف الدراسة الحالية إلى الكشف عن متطلبات المهام لدى معلم الطور الابتدائي وكذا تشخيص مصادر ضغوط العمل لديه. اعتمد الباحثان في دراستهما على تبني تقنية تحليل العمل في جمع البيانات المتعلقة بالدراسة، وتوصلا إلى وصف مهام المعلم العامة، المعرفية، النفسية والسلوكية، إضافة إلى تشخيص مصادر ضغوط العمل لديه والمتمثلة خاصة في الضغوط التنظيمية والاجتماعية. Abstract: The purpose of this study is to explore the main mission of the primary school teacher, in order to help the diagnostic of the job related stress and its causes. The research was based on the job analysis techniques, to assemble the data related to the study. This study concluded to the description of the primary school teacher’s job needs both psychological and cognitive. And being able to determine the stress resources related to the job, especially the social and organizational ones.
Keywords: متطلبات المهام، مصادر الضغط، معلم الطور الابتدائي. Stress; Job analysis; Job related stress.